World champions - Patterson, James; Fabares, Jay; Grabenstein, Chris (London Young Arrow, 2021)
Whenever there's a problem to solve, the kids work better together. so does an evil group of the rich and powerful who will do whatever it takes to split the kids up- even as the planet is changing before their eyes
Authers of the No. 1 New York times bestseller Max Einstein : the genius experiment
English stories
Keywords: Action and adventure fiction; English stories